Perioperative diabetes mellitus affects the outcomes of lung transplant recipients. (9th June 2022) - Yamada, Yoshito; Sato, Tosiya; Harada, Norio; Kayawake, Hidenao; Tanaka, Satona; Yutaka, Yojiro; Hamaji, Masatsugu; Nakajima, Daisuke; Ohsumi, Akihiro; Date, Hiroshi
Abstract: OBJECTIVES: Identifying the risks for chronic lung allograft dysfunction (CLAD) after lung transplantation (LTx) is beneficial to the patient. We hypothesized that diabetes mellitus (DM) is relevant to CLAD development. Our study aimed to clarify if DM is a risk for poor post-LTx outcomes. METHODS: The records of patients first undergoing LTx in our institution between 2010 and 2018 were reviewed retrospectively. Patient characteristics and postoperative outcomes were analysed. We established 6 months post-LTx as the landmark point for predicting overall survival (OS) and CLAD development. To identify perioperative DM, we evaluated the patient for DM at 6 months post-LTx. RESULTS: A total of 172 patients were investigated. DM and CLAD occurred in 76 and 39 patients, respectively, and 40 died. At 6 months post-LTx, the unadjusted and adjusted hazard ratios of DM for OS were 3.36 [95% confidence interval (CI) = 1.67–6.73] and 2.78 (95% CI = 1.35–5.75), respectively. The unadjusted and adjusted hazard ratios of DM for CLAD-free survival were 2.20 (95% CI = 1.27–3.80) and 2.15 (95% CI = 1.24–3.74). The patients with DM were older and had a higher body mass index and more incidents of post-LTx malignant disease than the non-DM patients. The 5-year OS and CLAD-free survival rates of the patients with or without DM were 57.2% vs 86.5% and 50.1% vs 72.9%, respectively. CONCLUSIONS: Perioperative DM was identified as an independent adverse factor for OS and CLAD-free survival. Perioperative management of DM should be emphasized in the clinical setting of LTx. Abstract : Lung transplantation (LTx) is a therapeutic option for patients with end-stage pulmonary diseases.